Experimental evidence for a mismatch between insect emergence and waterfowl hatching under increased spring temperatures. Issue 9 (30th September 2014) - Hansson, Lars-Anders; Ekvall, Mattias K.; Ekvall, Mikael T.; Ahlgren, Johan; Holm, William Sidemo; Dessborn, Lisa; Brönmark, Christer
Abstract : By combining a large‐scale experimental assessment on timing of insect emergence with long‐term monitoring of waterfowl hatching date, we here show that insect emergence is mainly driven by temperature, whereas there is only a weak effect of increasing spring temperatures on inter‐annual variability in observations of waterfowl chicks. Hence, a change in timing of the mass‐emergence of insects from lakes and wetlands, which is the crucial food source for waterfowl chicks, will likely result in a consumer/resource mismatch in a future climate change perspective. Specifically, we experimentally show that a moderate increase in temperature of 3°C above ambient, expected to occur within 25–75 years, leads to a considerably (2 weeks) earlier, and more pronounced, peak in insect emergence ( Chironomus sp). Moreover, by utilizing long‐term Citizen Science databases, ranging over several decades, we also show that common waterfowl species are unable to significantly adjust their reproduction to fit future temperature increase. Hence, based on our data we predict a future mismatch between insect emergence and waterfowl species basing their reproduction on temperature. This will have a profound impact on reproductive success and population dynamics of many aquatic birds, as well as on freshwater biodiversity.